Effect of oocyte morphology on post-warming survival and embryo development in vitrified autologous oocytes. Issue 3 (March 2019) - Coello, Aila; Sanchez, Eva; Vallejo, Begoña; Meseguer, Marcos; Remohí, José; Cobo, Ana
Abstract: Research question: Does the presence of dysmorphisms affect post-warming survival and embryo development in vitrified autologous oocytes? Design: A retrospective study comparing post-warming survival, fertilization and embryo development between morphologically normal ( n  = 269) and dysmorphic oocytes ( n  = 147). Results: The survival rate was 81.4% in the morphologically normal oocytes and 87.1% in the dysmorphic oocyte group (OR 1.53; 95% CI 0.86 to 2.72). The fertilization rate was 69.9 versus 66.4% (OR 0.85; 95% CI 0.53 to 1.36), the proportion of good-quality embryos on day 3 was 30.3% versus 32.0% (OR 1.08; 95% CI 0.59 to 1.97) and the blastocyst formation rate was 54.5% versus 60.5% (OR 1.27; 95% CI 0.60 to 2.72) for the morphologically normal and the dysmorphic oocytes group, respectively. No statistical differences were found when the number and type of dysmorphism were analysed. Conclusion: Oocyte dysmorphisms did not seem to affect survival, fertilization and embryo development in vitrified autologous oocytes, and yielded comparable results to the morphologically normal oocytes.